Chemoradiotherapy for Unresectable INI1-negative Chordoma in a Child. Issue 1 (January 2020) - Miyahara, Hiroyuki; Nodomi, Seishiro; Umeda, Katsutsugu; Itasaka, Satoshi; Waki, Kenji; Imai, Tsuyoshi
Abstract : The characteristics of chordomas in children are distinct from those in adults. In particular, the prognosis of patients with INI1-negative chordoma is dismal. The standard treatment for localized chordoma, complete surgical resection with a wide margin, is seldom feasible for chordomas arising at the clivus in children, mainly due to associated complications. Therefore, other treatments for unresectable chordomas in children, including chemoradiotherapy, must be explored. Here, we report a 7-year-old girl with an INI1-negative chordoma of the clivus, who responded to conventional chemotherapy plus radiotherapy. Without surgical resection, she remains alive after 1 year and 7 months of the initial diagnosis.